Susceptibility‐sensitive MRI of multiple sclerosis lesions and the impact of normal‐appearing white matter changes. (4th May 2017) - Wiggermann, Vanessa; Hametner, Simon; Hernández‐Torres, Enedino; Kames, Christian; Endmayr, Verena; Kasprian, Gregor; Höftberger, Romana; Li, David K.B.; Traboulsee, Anthony; Rauscher, Alexander
Abstract : Susceptibility‐sensitive magnetic resonance imaging (MRI) has gained importance in multiple sclerosis (MS) research because of its versatility, high resolution and excellent sensitivity to changes in tissue structure and composition. In particular, mapping of the resonance frequency of the MR signal and quantitative susceptibility mapping (QSM) have been explored for the description of MS lesions. Many current studies utilizing these techniques attribute increases in the MR frequency or QSM to elevated tissue iron content, in addition to myelin loss. However, this common interpretation is inconsistent with recent histopathological studies. Here, we investigate the nature of MR frequency shifts related to MS lesions by comparing post‐mortem MRI data with histology, and contrast them with numerical simulations of the MR signal. We demonstrate that iron accumulation is not the driving source of the MR frequency or QSM image contrast in our sample; rather, most chronic MS lesions are characterized by advanced loss of both myelin and iron. Moreover, our results suggest that the appearance of MS lesions on MR frequency maps and QSM depends on changes in the non‐lesional white matter surrounding the lesions. Understanding and accounting for these changes is essential for the quantitative interpretation of MR frequency or QSM data in white matter. Abstract : We investigated the nature of magnetic resonance (MR) frequency shifts related to multiple sclerosis (MS) lesions by comparing post‐mortem MR imaging data with histology, and contrasted them with numerical simulations. We demonstrated that most MS lesions are characterized by advanced myelin and iron loss, and showed that the appearance of MS lesions on MR frequency and quantitative susceptibility mapping (QSM) images depends on changes in the normal‐appearing white matter surrounding the lesions, making it essential to account for these changes.